Supervision in Motivational Interviewing: An Exploratory Study. Issue 4 (20th March 2017) - Beckman, Maria; Bohman, Benjamin; Forsberg, Lars; Rasmussen, Finn; Ghaderi, Ata
Abstract : Background: Although supervision is believed to be an important strategy for training practitioners in evidence-based practice, little is known about how it should be organized and conducted to promote implementation fidelity.Aims: To explore supervisor behaviours that might facilitate supervisees' proficiency in motivational interviewing.Method: In this exploratory study, ten supervisors from a primary prevention intervention of childhood obesity responded to semi-structured interviews about their supervision behaviours. A mixed method approach was used; both qualitative and quantitative data were collected and analysed.Results: The supervisors reported using several sources of information for evaluating and providing systematic feedback on supervisees' performance. However, the majority did not use the available objective measures of proficiency as the primary source. Moreover, half of the supervisors argued that objective feedback might have a punishing effect on the supervisees.Conclusions: Variation in the use of supervision components that previous research has proposed to be potentially influential to the process and outcome may lead to less efficient supervision. Findings suggest that appropriate supervision activities conducted in each supervision session require clear supervision principles that specify the content and procedure of the supervision, as well as regular adherence monitoring of the supervision sessions.